Rural and urban differences in lifestyle behaviors: a baseline survey among type II diabetic patients in an integrated nutritional supports program to combat obesity - Rahim, Abu Naim Mohammad Bazlur; Huq, A.K. Obidul; Anzin, Farjana (Progress in Nutrition, 2023)
Background and aims: Recently, the prevalence of type II diabetes and obesity has increased in both rural and urban communities. The aim of this work is to investigate the lifestyle behaviors including food consumption, physical exercise and sleep duration among type II diabetic patients in an integrated nutritional support program in rural and urban settings in Bangladesh. Methodology: A baseline cross-sectional study was conducted among 512 rural and 712 urban type-II diabetes patients from two different communities. Information about the participants’ socio-economic and dietary patterns, duration of physical exercise, duration of sleep and body mass index (BMI) measurement were collected by related appropriate techniques. Data were analyzed by SPSS software. Results: The prevalence of obesity (BMI≥30) among the type-II diabetic patients was significantly different between the two community settings (rural 60.9% vs. urban 69.2%). Food consumption for the energy-giving, processed foods and beverages groups significantly differs from the rural and urban settings. However, consumption of body-building and protective foods in both communities was lowered compared to the present dietary guidelines and did not show significant differences. The average contribution of different food groups’ consumption was: energy giving 69.8% and 60.1%, body-building 12.4% and 13.3%, and protective foods 13.7% and 11.2% respectively for the rural and urban populations. Both males and females slept less than the recommended hours, without any significant variations among the rural and urban lifestyles. The duration of physical exercise was significantly (p <0.05), differed in both settings and the mean duration of physical exercise per day was 32 ±9 minutes in the rural and 23±7 minutes in the urban area. Conclusions: Imbalanced lifestyles through poor food consumption patterns, insufficient sleep and physical exercise may predispose to type II diabetes and obesity, therefore, proper nutrition education programs should be developed concerning lifestyle behaviors.